The First Lady and the rebel : a novel - Higginbotham, Susan (Sourcebooks Landmark, 2019)
A Union's First Lady. As the Civil War cracks the country in two, Mary Lincoln stands beside her husband praying for a swift Northern victory. But as the body count rises, Mary can't help but fear each bloody gain. Because her beloved sister Emily is across party lines, fighting for the South, and Mary is at risk of losing both her country and her family in the tides of a brutal war. A Confederate Rebel's Wife. Emily Todd Helm has married the love of her life. But when her husband's southern ties pull them into a war neither want to join, she must make a choice. Abandon the family she has built in the South or fight against the sister she has always loved best. With a country's legacy at stake, how will two sisters shape history?